P83 CYP2D6 phenotyping in children treated with tramadol at the Emergency Department. Issue 6 (17th May 2019) - Rodieux, F; Storelli, F; Manzano, S; Gervaix, A; Posfay-Barbe, K; Samer, C; Daali, Y; Desmeules, J
Abstract : Background: Pain management is essential and opioids side effects are of major concern. Tramadol safety and efficacy is influenced by CYP2D6 activity. Phenotyping measurement is available to assess CYP2D6 activity and allow a safe precision medicine approach. 4 However need for administration of a probe drug and invasive sampling limit its use. Our objective is to evaluate direct measurement of M1/tramadol ratio and pupillometry as phenotyping methods to identify CYP2D6 ultrarapid (UM) and poor (PM) metabolizers in children treated with tramadol. 1-6 Methods: We plan to include 53 children receiving their 1st dose of tramadol at the Emergency Department (ED) of the Geneva Children's Hospital. Children with concomitant inhibitors/inducers of CYP2D6 and CYP3A or drug with an impact on pupil size are exclude. Standard CYP2D6 phenotyping is performed by measuring blood dextrorphan/dextromethorphan (DOR/DEM) using dried blood spots (DBS) at least 90min after dextromethorphan and tramadol administration. Tramadol and its active metabolite, M1, concentrations are also performed using DBS at the same time. Pupillometry is performed at time of tramadol administration and 1 to twice per hour, during the stay in the ED. Results: We included 26 children, median age 10.7 years, of which 2 are UM (8%) and 3 PM (12%), corresponding to what is expected in the Caucasian population. We found a positive correlation between DOR/MED and M1/tramadol ratio (R 2 = 0.389, p = 0.0006). Pupillometry analyses are in progress. Tramadol 2 mg/kg orally was well tolerated in all children, including UM and PM. Conclusion: Our study shows that it is possible to determine CYP2D6 activity in order to provide safe and effective tramadol prescription in children in a less invasive manner than by administering a probe drug, by directly determining the metabolic ratio between tramadol and its metabolite, M1 in children treated with tramadol References: Fliegert, F., B. Kurth, and K. Gohler, The effects of tramadol on static and dynamic pupillometry in healthy subjects-the relationship between pharmacodynamics, pharmacokinetics and CYP2D6 metaboliser status Eur J Clin Pharmacol, 2005. 61(4): p. 257–66. Slanar, O., et al., CYP2D6 polymorphism, tramadol pharmacokinetics and pupillary response Eur J Clin Pharmacol, 2006. 62(1): p. 75–6; author reply 77–8. Slanar, O., et al., Miotic action of tramadol is determined by CYP2D6 genotype Physiol Res, 2007. 56(1): p. 129–36. Kirchheiner, J., et al., Effects of the CYP2D6 gene duplication on the pharmacokinetics and pharmacodynamics of tramadol J Clin Psychopharmacol, 2008. 28(1): p. 78–83. Matouskova, O., et al., Pupillometry in healthy volunteers as a biomarker of tramadol efficacy J Clin Pharm Ther, 2011. 36(4): p. 513–7. Connelly, M.A., et al., Pupillometry: a non-invasive technique for pain assessment in paediatric patients Arch Dis Child, 2014. 99(12): p. 1125–31. Disclosure(s): Nothing to disclose